2020
DOI: 10.1016/j.ebiom.2019.11.033
|View full text |Cite
|
Sign up to set email alerts
|

Airway epithelial cell differentiation relies on deficient Hedgehog signalling in COPD

Abstract: Background: Hedgehog (HH) pathway is constantly under scrutiny in the context of organ development. Lung morphogenesis requires HH signalling which participates thereafter to the pulmonary homeostasis by regulating epithelial cell quiescence and repair. Since epithelial remodelling is a hallmark of Chronic Obstructive Pulmonary Disease (COPD), we investigated whether the main molecular actors of HH pathway participate to airway epithelial cell differentiation and we analysed their alterations in COPD patients.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
29
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 85 publications
(105 reference statements)
5
29
0
Order By: Relevance
“…Our results are consistent with our previous observations showing that prevention of ligand-induced HH activation resulted in epithelial remodelling with an increased number of basal cells and decreased ciliogenesis [15], therefore mimicking the remodelling features of COPD observed in endobronchial samples in our study.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Our results are consistent with our previous observations showing that prevention of ligand-induced HH activation resulted in epithelial remodelling with an increased number of basal cells and decreased ciliogenesis [15], therefore mimicking the remodelling features of COPD observed in endobronchial samples in our study.…”
Section: Discussionsupporting
confidence: 93%
“…In concordance with our recent observations on FFPE tissues from lung resections [15], Ptch1, the receptor responsible for transduction of Shh signalling, was also found on non-differentiated and differentiated cells from isolated AEC and biopsies. Gli2 may be found in basal AEC nuclei, but can also be observed subciliary in ciliated cells, suggesting the presence of autocrine and paracrine signalling in the epithelium.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Although both NOTCH1 and NOTCH3 have been implicated in regulating the balanced differentiation of airway basal cells between the secretory and ciliated cell fates (Tsao et al, 2009;Gomi et al, 2015), both NOTCH3 and HEY1 mRNA expression was significantly decreased in the small airway epithelium of COPD patients (Tilley et al, 2009), while increased expression levels of activated NOTCH1 and the effector HEY2 were observed in COPD airways and mutant murine lungs and were associated with decreased numbers of ciliated cells and increased goblet cell metaplasia and mucus overproduction (Guseh et al, 2009;Boucherat et al, 2012), suggesting that NOTCH1 and NOTCH3 may play distinct roles in regulating airway epithelial differentiation and proliferation. Previous studies have demonstrated that enhanced squamous metaplasia and goblet cell hyperplasia as well as reduced ciliogenesis are all correlated with increased NOTCH signaling and are implicated in the COPD airways (Pilette et al, 2001;Guseh et al, 2009;Boucherat et al, 2012;Barnes, 2015;Gohy et al, 2019;Belgacemi et al, 2020). It has also been shown recently that reduced ciliogenesis in COPD airways is associated with overexpressed TGF-β1 and deficient Sonic hedgehog (Shh)/Gli2/Smo signaling (Gohy et al, 2019;Belgacemi et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that enhanced squamous metaplasia and goblet cell hyperplasia as well as reduced ciliogenesis are all correlated with increased NOTCH signaling and are implicated in the COPD airways (Pilette et al, 2001;Guseh et al, 2009;Boucherat et al, 2012;Barnes, 2015;Gohy et al, 2019;Belgacemi et al, 2020). It has also been shown recently that reduced ciliogenesis in COPD airways is associated with overexpressed TGF-β1 and deficient Sonic hedgehog (Shh)/Gli2/Smo signaling (Gohy et al, 2019;Belgacemi et al, 2020). In this study, we show for the first time that NOTCH1 and NOTCH3 expression levels in the COPD airway epithelium are differentially regulated and respectively correlated with overexpression of the goblet cell marker MUC5AC and deficiency of the ciliated cell marker FOXJ1 (Figures 5, 7, 8).…”
Section: Discussionmentioning
confidence: 99%